Immunopathogenesis and Cellular Interactions in Human T-Cell Leukemia Virus Type 1 Associated Myelopathy/Tropical Spastic Paraparesis - Aghajanian, Sepehr; Teymoori-Rad, Majid; Molaverdi, Ghazale; Mozhgani, Sayed-Hamidreza (Frontiers in Microbiology, 2020)
HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP) is a neuropathological disorder in 1–3% of individuals infected with Human T-lymphotropic virus 1 (HTLV-1). This condition is characterized by progressive spastic lower limb weakness and paralysis, lower back pain, bladder incontinence, and mild sensory disturbances resembling spinal forms of multiple sclerosis. This disease also causes chronic disability and is therefore associated with high health burden in areas where HTLV-1 infection is endemic. Despite various efforts in understanding the virus and discovery of novel diagnostic markers, and cellular and viral interactions, HAM/TSP management is still unsatisfactory and mainly focused on symptomatic alleviation, and it hasn’t been explained why only a minority of the virus carriers develop HAM/TSP. This comprehensive review focuses on host and viral factors in association with immunopathology of the disease in hope of providing new insights for drug therapies or other forms of intervention.